2005
DOI: 10.1038/sj.bjc.6602566
|View full text |Cite
|
Sign up to set email alerts
|

No association between fruit or vegetable consumption and the risk of colorectal cancer in Japan

Abstract: In a pooled analysis of two prospective studies with 88 658 Japanese men and women, fruit and vegetable consumptions, were not associated with a lower risk of colorectal cancer (705 cases); multivariate relative risk (95% confidence interval) for the highest vs the lowest quartile of intake being 0.92 (0.70 -1.19) and 1.00 (0.79 -1.27), respectively. (Michels et al, 2000;Voorrips et al, 2000). In Japan, mortality from colorectal cancer increased during 1950 -2000, especially in men (age-adjusted rate per 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 4 publications
2
24
1
2
Order By: Relevance
“…Further adjustment was made for intake of energy-adjusted dietary fiber (in quartiles), total folate (in quartiles) and red meat (in quartiles). These variables are either known or suspected risk or preventive factors for colorectal cancer [20,[23][24][25][26][27][28][29][30]. Additional adjustment for intake of energy-adjusted total calcium and vitamin D produced no appreciable change in the results and these variables were excluded from the final model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further adjustment was made for intake of energy-adjusted dietary fiber (in quartiles), total folate (in quartiles) and red meat (in quartiles). These variables are either known or suspected risk or preventive factors for colorectal cancer [20,[23][24][25][26][27][28][29][30]. Additional adjustment for intake of energy-adjusted total calcium and vitamin D produced no appreciable change in the results and these variables were excluded from the final model.…”
Section: Discussionmentioning
confidence: 99%
“…However, the characteristics of subjects with and without missing information did not differ. Although unmeasured confounders may not have been controlled in this study, lifestyle factors and dietary habits identified as potential confounding factors possibly associated with colorectal cancer in previous reports were accounted for [20,[23][24][25][26][27][28][29][30], with the expectation that statistical adjustment might be to some degree possible if information on associated variables were available.…”
Section: Discussionmentioning
confidence: 99%
“…5 This questionnaire was developed for use in a wide range of studies of diet and health in Scotland, and the validity for ranking macronutrients and micronutrients in younger adults have been previously described (31). In particular, it has been validated against serum phytoestrogen concentrations (ref.…”
Section: Methodsmentioning
confidence: 99%
“…Results from more recent cohort studies are inconclusive. Some cohort studies reported no or little effect of vegetable or fruit intake on colorectal cancer risk (5)(6)(7). However, in the Nurses' Health study, an inverse association between fruit consumption and colorectal adenomas was identified (8), and in a population-based prospective study of women in central Sweden, individuals who consumed very low amounts of fruit and vegetables had the greatest risk of colorectal cancer (9).…”
Section: Introductionmentioning
confidence: 99%
“…The questionnaires had 6 frequency categories for beverages, ranging from 'rarely' to '5 glasses per day', and 4 (Cohort I) or 5 (Cohort II) categories for other items, ranging from 'never' or 'rarely' to 'almost daily'. The intakes of total energy, vegetables, fruit, and fish were calculated from these responses (26,27), and portion sizes were estimated using data from a validation study (28).…”
Section: Questionnaire Surveymentioning
confidence: 99%